Micro-Flow Sensor Design and Implementation Based on Diamagnetic Levitation - Aydemir, Gizem; Erozer, Can; Uvet, Huseyin (IEEE, 2018)
This contribution presents a concept for the measurement of flow with laser sensor and magnetic levitation in microfluidic systems. Modelling of the flow and physical property diagnosis is crucial in microfluidic system design. The system is based on the displacement measurement of a levitated magnet in a channel with a laser sensor. On a pyrolytic graphite in the channel, levitation of the magnet in the channel is fixed by a ring magnet (NdFeB). The ring magnet is controlled by a micro stage that allows movement in z axis. Displacement in x axis is observed when variant flow rates are applied to the levitated magnet. Displacements are determined via laser sensor. Pressure and displacement values under flow and magnetic field are determined with multiphysics via FEM program (COMSOL). Displacement of the magnet is detected by the designed flow sensor; and the flow rate is detected by numerical analysis method using the data taken from the laser sensor with a C# program.
Keywords: microflow; microflow sensor; sensor; magnetic levitation; diamagnetic levitation; pyrolytic graphite; Automation & Control Systems; Computer Science; Engineering